Polished stone value of aggregates and its relationship to mineralogy and grain size / Juraidah Ahmad … [et al.] - Ahmad, Juraidah; Abdul Rahman, Mohd Yusof; Adnan, Muhammad Akram; Ahmad, Azura (2004)
Safe and durable roads are the main aim of highway engineers and are directly related to the road surface especially where skidding is of much concern. The use of geological material represents a large proportion especially in construction of highways which is focused on the use of rock aggregates in the pavement structure. The skidding resistance is very much related to the types of aggregates used in the pavement material, therefore, thorough understanding and basic knowledge to ensure materials selection and used for pavement construction is correctly specified and gives optimal results is of high importance. The study focused on the various types of texture and mineralogy of aggregates from different quarries in the Klang Valley which shows variation on the skid resistance as measured using the Polished Stone Value (PSV) test in the laboratory. Measuring the polishing action of vehicle tyre under conditions similar to those occurring on the surface of road is vital to determine principally the inherent qualities of the aggregate which is one of the main ingredients of pavement. This has lead to effort into identifying, ranking and locating quality aggregates most suitable for road construction which varies from high specification aggregate to aggregates which possess the minimum requirement. The study on the petrography in relation to the PSV of the aggregate is focused. Findings show there is variability in the PSV with different quartz and material matrix of the aggregate. A positive relationship is noticeable from petrography test showing percentage of quartz content in relation to PSV.